Literature Review: Development Of Augmented Reality-Based E-Modules In Science Learning To Enhance Elementary Students’ Critical Thinking Skills - Muhammad Fathul Fuadi; Wasino Wasino; Nuni Widiarti; Bambang Subali (Publikasi Pendidikan, 2026)
This study is a literature review that analyzes previous research on the development of Augmented Reality (AR)-based E-Modules in science learning (IPA) at the elementary school level, with a focus on enhancing students’ critical thinking skills. The study employed a Systematic Literature Review (SLR) method guided by the PRISMA protocol. Articles were collected from databases such as Google Scholar, ERIC, and ScienceDirect, using inclusion criteria that included publications from 2020 to 2025, written in Indonesian or English, and discussing the development or implementation of AR-based E-Modules in elementary education. From a total of 413 identified articles, 35 met the inclusion criteria and were analyzed further. The findings indicate that AR-based E-Modules consistently improve learning engagement, conceptual understanding in science, and students’ critical thinking skills through interactive visualization and immersive learning experiences. Moreover, integrating AR in E-Modules supports deep learning and student-centered learning approaches. The review suggests that future development of AR-based E-Modules should emphasize interactivity, usability, and alignment with the national curriculum to maximize their potential in fostering critical thinking among elementary school students.